Discovery and preclinical evaluation of BPB-101: a novel triple functional bispecific antibody targeting GARP-TGF-β complex/SLC, free TGF-β and PD-L1 - Xu, Wenxin; Xu, Jieying; Li, Pingcui; Xu, Deyu; Cheng, Hongjie; Zheng, Huan; Zhang, Li; Liu, Mengmeng; Ye, Siyuan; Jiang, Mengshi; Yu, Wenqi; Wang, Jiabing; et al. (Frontiers in Immunology, 2024)
BackgroundIn the tumor microenvironment (TME), the transforming growth factor-β (TGF-β) and programmed cell death receptor 1 (PD-1)/programmed death ligand 1 (PD-L1) signaling axes are complementary, nonredundant immunosuppressive signaling pathways. Studies have revealed that active TGF-β is mainly released from the glycoprotein A repetitions predominant (GARP)-TGF-β complex on the surface of activated regulatory T cells (Tregs), B cells, natural killer (NK) cells, and tumor cells. The currently available antibodies or fusion proteins that target TGF-β are limited in their abilities to simultaneously block TGF-β release and neutralize active TGF-β in the TME, thus limiting their antitumor effects.MethodsWe designed and constructed a bispecific, trifunctional antibody, namely, BPB-101, that specifically targets the GARP-TGF-β complex and/or small latent complex (SLC), active TGF-β, and PD-L1. The binding ability of BPB-101 to the different antigens was determined by ELISA, FACS, and biolayer interferometry (BLI). The blocking ability of BPB-101 to the TGF-β and PD-1/PD-L1 signaling axes was determined by reporter gene assay (RGA). The antitumor effect and biosafety of BPB-101 were determined in a transgenic mouse tumor model and cynomolgus monkeys, respectively. Stability assessments, including stability in serum, after exposure to light, after repeated freeze-thaw cycles, and after high-temperature stress tests had been completed to evaluate the stability of BPB-101.ResultsBPB-101 bound efficiently to different antigenic proteins: the GARP-TGF-β complex and/or SLC, active TGF-β, and PD-L1. Data showed that BPB-101 not only effectively inhibited the release of TGF-β from human Tregs, but also blocked both the TGF-β and PD-1/PD-L1 signaling pathways. In an MC38-hPD-L1 tumor-bearing C57BL/6-hGARP mouse model, BPB-101 at a dose of 5 mg/kg significantly inhibited tumor growth, with a complete elimination rate of 50%. Stability assessments confirmed the robustness of BPB-101. Furthermore, BPB-101 showed a favorable safety profile in nonhuman primate (NHP) toxicity studies.ConclusionBPB-101 is a potentially promising therapeutic candidate that may address unmet clinical needs in cancer immunotherapy, thus, BPB-101 warrants further clinical investigation.